Evangelical and Catholic Masculinities in Two Fatherhood Ministries - Gelfer, Joseph (Feminist theology, 2010)
In men’s ministries it is possible to distinguish between evangelical and Catholic masculinities: the former being more traditional, the latter somewhat ‘softer.’ This paper pursues these differing masculine performances within a discourse of fatherhood in two fatherhood ministries: Dad the Family Shepherd and Fathers for Good. On the whole, the fatherhood ministries repeat the evangelical and Catholic masculinities of regular men’s ministries via the treatment of male headship, the politics of gender and sexuality, and the use of sport as a signifier for masculinity.